Model Application of Accounting Information Systems of Spare Parts Sales and Purchase on Car Service Company - Christian, Lianawati (Bina Nusantara University, 2015)
The purpose of this research is to analyze accounting information systems of sales and purchases of spare parts in general car service companies and to identify the problems encountered and the needs of necessary information. This research used literature study to collect data, field study with observation, and design using UML (Unified Modeling Language) with activity diagrams, class diagrams, use case diagrams, database design, form design, display design, draft reports. The result achieved is an application model of accounting information systems of sales and purchases of spare parts in general car service companies. As a conclusion, the accounting information systems of sales and purchases provides ease for management to obtain information quickly and easily as well as the presentation of reports quickly and accurately.